2018
DOI: 10.1177/0954408918756654
|View full text |Cite
|
Sign up to set email alerts
|

Multi-criteria optimization of weld bead in pulsed Nd:YAG laser welding of stainless steel 316

Abstract: Laser welding is widely used for its advantages like deeper weld penetration, narrow heat affected zone, higher welding speeds and better weld quality with less damage to the workpiece compared to arc welding processes. The purpose of this paper is to determine the influence of major laser welding process parameters of beam pulse energy, travel speed and focal position on weld fusion zone geometry in stainless steel and optimizing these parameters to obtain maximum penetration and minimum weld width simultaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…However, due to the recrystallization of the material and due to the melting at the spot weld, softening occurred in the HAZ and fusion zones presenting lower values of hardness than the base material. Solati et al [ 41 ] reported a reduction in the hardness results from the BM forward to the center of the FZ due to changes in microstructure in laser seam welds of AISI316L sheet of 0.6 mm of thickness. The microstructure observed in this study has also been observed in other stainless steels (i.e., AISI304, AISI316) seam welded by an Nd-YAG laser [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the recrystallization of the material and due to the melting at the spot weld, softening occurred in the HAZ and fusion zones presenting lower values of hardness than the base material. Solati et al [ 41 ] reported a reduction in the hardness results from the BM forward to the center of the FZ due to changes in microstructure in laser seam welds of AISI316L sheet of 0.6 mm of thickness. The microstructure observed in this study has also been observed in other stainless steels (i.e., AISI304, AISI316) seam welded by an Nd-YAG laser [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The generic methodology adopted in Taguchi-based GRA is depicted in Figure 1. The detail of the process can be found elsewhere in the literature [28][29][30][31][32][33][34][35]. The selection of a suitable design matrix depends upon the number of factors, their levels, and the interaction of interest.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the manufacturing system of the INTERLASE project covers a number of scientific domains, starting with, but not limited to, computer aided process planning (CAPP), process control, laser processing (cutting, welding, forming, and other laser processes), sequencing, and process monitoring. Looking at the core processes, both laser cutting and laser welding are established manufacturing processes with extensive research being conducted in process-related phenomena [29] [30], process optimization [31], scheduling, and integration [32] [28]. In contrast, laser forming is primarily receiving academic interest and is yet to be utilized in manufacturing.…”
Section: Project Challengesmentioning
confidence: 99%